Environmental Risk Factors Implicated in Liver Disease: A Mini-Review - Melaram, Rajesh (Frontiers in Public Health, 2021)
Liver disease is a global health issue, resulting in about two million deaths per year. It encompasses a wide spectrum of varied or unknown etiologies, ranging from lifestyle choices to pre-existing comorbidities. In recent decades, exposure to environmental toxins and subsequent liver health outcomes have captured public interest, due to the extensive application of pesticides, consumption of aflatoxin contaminated foodstuff, and cyanobacterial harmful algae blooms in endemic regions of liver disease. Hepatocellular carcinoma is a serious and debilitating condition of the liver, characterized by abdominal pain and unexplained weight loss. Established risk factors for hepatocellular carcinoma include alcohol consumption, cigarette smoking, and viral infections of hepatitis B and C. However, mounting evidence suggests that environmental toxins may represent an important contributing factor in hepatocellular carcinoma development. This mini-review synthesizes epidemiological investigations, providing evidence for environmental toxins as one potential risk factor for liver disease.